η6-arene-zirconium-pnp-pincer complexes: mechanism of their hydrogenolytic formation and their reactivity as zirconium(ii) synthons$ddedicated to Prof. Frank H. Köhler on the occasion of his 75th birthday - Plundrich, Gudrun; Wadepohl, Hubert; Clot, Eric; Gade, Lutz H. (Chemistry - a European journal, 2016)
The cyclometalated monobenzyl complexes [(CbzdiphosR-CH)ZrBnX] 1 iPrCl and 1 PhI reacted with dihydrogen (10 bar) to yield the η6-toluene complexes [(CbzdiphosR)Zr(η6-tol)X] 2 iPrCl and 2 PhI (cbzdiphos=1,8-bis(phosphino)-3,6-di-tert-butyl-9H-carbazole). The arene complexes were also found to be directly accessible from the triiodide [(CbzdiphosPh)ZrI3] through an in situ reaction with a dibenzylmagnesium reagent and subsequent hydrogenolysis, as exemplified for the η6-mesitylene complex [(CbzdiphosPh)Zr(η6-mes)I] (3 PhI). The tolyl-ring in 2 iPrCl adopts a puckered arrangement (fold angle 23.3°) indicating significant arene-1,4-diido character. Deuterium labeling experiments were consistent with an intramolecular reaction sequence after the initial hydrogenolysis of a Zr−C bond by a σ-bond metathesis. A DFT study of the reaction sequence indicates that hydrogenolysis by σ-bond metathesis first occurs at the cyclometalated ancillary ligand giving a hydrido-benzyl intermediate, which subsequently reductively eliminates toluene that then coordinates to the Zr atom as the reduced arene ligand. Complex 2 PhI was reacted with 2,6-diisopropylphenyl isocyanide giving the deep blue, diamagnetic ZrII-diisocyanide complex [(CbzdiphosPh)Zr(CNDipp)2I] (4 PhI). DFT modeling of 4 PhI demonstrated that the HOMO of the complex is primarily located as a “lone pair on zirconium”, with some degree of back-bonding into the C≡N π* bond, and the complex is thus most appropriately described as a zirconium(II) species. Reaction of 2 PhI with trimethylsilylazide (N3TMS) and 2 iPrCl with 1-azidoadamantane (N3Ad) resulted in the formation of the imido complexes [(CbzdiphosR)Zr=NR′(X)] 5 iPrCl-NAd and 5 PhI-NTMS, respectively. Reaction of 2 iPrCl with azobenzene led to N−N bond scission giving 6 iPrCl, in which one of the NPh-fragments is coupled with the carbazole nitrogen to form a central η2-bonded hydrazide(−1), whereas the other NPh-fragment binds to zirconium acting as an imido-ligand. Finally, addition of pyridine to 2 iPrCl yielded the dark purple complex [(CbzdiphosiPr)Zr(bpy)Cl] (7 iPrCl) through a combination of CH-activation and C−C-coupling. The structural data and UV/Vis spectroscopic properties of 7 iPrCl indicate that the bpy (bipyridine) may be regarded as a (dianionic) diamido-type ligand.
Im Titel ist Eta als griechischer Buchstabe dargestellt
Gesehen am 29.10.2020
Keywords: Festschrift